Socio-hygienic aspects of abortions among women of reproductive age - Kystaubaeva, Z.T.; Akhmetova, M.Zh.; Eliby, S. (Fundamental and Experimental Biology, 2017)
Latter research presents that various defects of reproductive performance, which negatively affect fetus formation and development, in 20-30% of cases are caused by the artificial abortion. With increasing number of abortions the probability of mortinality, natality of premature infant, and his mortality during the first week of life is raised. Despite the decreased total number of abortions, its level remains high. In the Republic of Kazakhstan against low birth-rate every 7th abortion (13,9) is done to primigravida. Abortion — today one of the most discussed topics in the world. Аlso the most controversial and contested issue among women of reproductive age. In today’s world the permissibility of abortion and its limits is one of the most controversial issues, including religious, ethical, medical, social and legal aspects. Analysis of the literature will clarify the social, moral, medical aspects in this field. This showed that the society can not find common ground and agree once and for all about this problem.